TRANSLATION TECHNIQUES OF TWIN FORMULAS PROVERBS INTO INDONESIAN - Jatmika, I Made Joni (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana; Vol 22 (2015): March 2015, 2015)
This study was aimed at describing the unique characteristics of twin formulas and analyzing translation techniques applied. The meaning equivalence within the twin formulas was analyzed based on denotative and connotative approach. Library research and qualitative method were used in this study. The proverbs being analyzed were taken from a bilingual self-help book, entitled “Awaken the Giant Within” written by Robbins (1991) and its translation Bangunkan Kuasa Raksasa di Dalam Diri translated by Saputra (2006). The theory about proverb types proposed by Mieder (2004) was used as the main theory. Translation theory proposed by Vinay and Dalbernet (2002) were used to analyze the translation techniques. In relation to denotative and connotative meaning of proverbs, meaning equivalence theory proposed by Leech (1974) was used to support the analysis. The collected data showed that there were 15 of 113 data were recognized having the characteristics of twin formulas. Alliterative and opposite patterns were found as variation of twin formulas. The literal translation was the translation technique mostly used. Besides, transposition, modulation and borrowing techniques were employed. Related to the meaning of proverbs, most forms were transferred denotatively.
Keywords: Proverbs, translation techniques, meaning equivalence, twin formulas, alliterative and opposite patterns